Research on the Vapor Injection of Two-stage Rotary Compressor. (August 2019) - Hu, Y S; Wei, H J; Yu, B; Yang, O X; Wang, J; Wu, J
Abstract: In order to understand the vapor injection flow characteristics of two-stage rotary compressor in the course of compression, a mathematical model based on mass conservation equation, energy equation and thermodynamic identity was established and proved by P-V diagram testing results. Some useful conclusions about pressure in the intermediate chamber and mass flow of vapor injection in the course of compression were also given out. The results show that, gas backflow between the intermediate chamber and the vapor injection channel is an important defection of two-stage rotary compressor which can be solved by the application of injection valve in vapor injection channel. The injection valve can obviously reduce the gas backflow and the power loss in the course of compression while increasing the pressure fluctuation in the intermediate chamber. Experiments show that the COP of two-stage rotary compressor with the injection valve increased by over 2% in ASHRAE/T working condition.